Psychiatry Clerkship Self-Assessment: Psychosis, Dementia and Child & Adolescent Practice Vignettes - Adriana Foster; Donna Londino (Association of American Medical Colleges, 2010)
Abstract This resource presents four clinical vignettes on psychosis and dementia. The vignettes were developed to provide junior clerks with a reinforcement of knowledge acquired in lectures and clinical patient encounters during psychiatry rotation. The objective of these exercises is to stimulate self-directed learning about psychosis due to treatment with dopamine agonists, dementia with delusions and hallucinations, disruptive disorders of childhood, and mental retardation. The rationale is to allow junior clerks to self-assess their knowledge of these disorders and receive immediate feedback on their performance, as well as to prepare them for the National Board of Medical Examiner's subject exam (the SHELF exam) administered at the end of the clerkship. The exercises were constructed in the National Board of Medical Examiner's sequential item set test format. We envision that these vignettes can be used for self-directed learning or can be presented as pre- and posttests for lectures with respective topics.